Dynamics of Multilingual Environment in the Development of Students' Speaking Skills in Indonesian for Foreign Speakers - Putri Nurul Baeti; Laily Nurlina; Eko Muharudin; Isnaeni Praptanti (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the dynamics of a multilingual environment and its role in developing Indonesian speaking skills of students in the Indonesian for Foreign Speakers (BIPA) program. The research was conducted at Universitas Muhammadiyah Purwokerto in the 2024/2025 academic year. The population of this study consisted of all foreign students enrolled in the BIPA program at Universitas Muhammadiyah Purwokerto, with the sample selected purposively, namely students who actively participated in BIPA classes and interacted with the campus environment and surrounding community. This study employed a qualitative method with a case study design. The research instruments included semi-structured interview guidelines and observation sheets. Data were analyzed qualitatively using thematic analysis through the stages of data reduction, data display, and conclusion drawing. The findings indicate that BIPA students are situated in a multilingual environment involving the use of Indonesian, local languages, and foreign languages. The environment functions as a source of language acquisition through out-of-class interactions, particularly through imitation and repetition. Formal learning provides linguistic foundations, while naturalistic learning supports speaking fluency and confidence. However, the dominance of local languages and affective factors pose challenges in oral communication.